2008
DOI: 10.1128/jb.01804-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Agmatine and Putrescine Catabolism inPseudomonas aeruginosaPAO1

Abstract: Polyamines (putrescine, spermidine, and spermine) are major organic polycations essential for a wide spectrum of cellular processes. The cells require mechanisms to maintain homeostasis of intracellular polyamines to prevent otherwise severe adverse effects. We performed a detailed transcriptome profile analysis of Pseudomonas aeruginosa in response to agmatine and putrescine with an emphasis in polyamine catabolism. Agmatine serves as the precursor compound for putrescine (and hence spermidine and spermine), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 38 publications
3
92
0
Order By: Relevance
“…Other transporters that the 11 acI SAGs have in common, include ABC-type transporters for ribose/xylose/ arabinose/galactoside, polyamines, dipeptides and branched-chain amino acids ( Table 2). The polyamine transporters are likely being used for putrescine uptake, as the SAGs harbor downstream pathways for its eventual conversion to succinate via the transamination pathway (Dasu et al, 2006;Chou et al, 2008); (Figure 2). Genes for the uptake of carboxylic acids in acI-A1, acI-A7 and acI-B1 were not found in any of the sequenced genomes, consistent with MAR-FISH-based studies (Buck et al, 2009;Salcher et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Other transporters that the 11 acI SAGs have in common, include ABC-type transporters for ribose/xylose/ arabinose/galactoside, polyamines, dipeptides and branched-chain amino acids ( Table 2). The polyamine transporters are likely being used for putrescine uptake, as the SAGs harbor downstream pathways for its eventual conversion to succinate via the transamination pathway (Dasu et al, 2006;Chou et al, 2008); (Figure 2). Genes for the uptake of carboxylic acids in acI-A1, acI-A7 and acI-B1 were not found in any of the sequenced genomes, consistent with MAR-FISH-based studies (Buck et al, 2009;Salcher et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Even in polyamine biosynthesis, there is a precedent for bypassing metabolic blocks. The Pseudomonas aeruginosa PAO1 N-carbamoylputrescine amidohydrolase gene deletion produced a leaky biosynthetic phenotype, and it was consequently found that acetylputrescine amidohydrolase, which has a very similar substrate to N-carbamoylputrescine (26), is induced in the gene deletion mutant and allows bypass of the metabolic block. The CANSDH/ CASDH enzyme is related to homospermidine synthase, lysine 6-dehydrogenase, saccharopine dehydrogenase, and aspartate dehydrogenase (6).…”
Section: Discussionmentioning
confidence: 99%
“…6, supplemental Table 8). Slr1022 shows strong similarity to the proteins (YgjG and SpuC) involved in degradation of putrescine into aminobutyrate in E. coli and Pseudomonas (55,56). Further evidence that succinate is produced from arginine came from the strong up-regulation of succinate dehydrogenase and malate dehydrogenase (Fig.…”
Section: Alternate Pathway For Assimilation Of Nitrogen and Carbon Unmentioning
confidence: 99%
“…Putrescine is known to play a critical role in DNA, RNA, and protein synthesis, as well as in cell proliferation and differentiation. Furthermore, putrescine serves as a source for carbon and nitrogen in E. coli and Pseudomonas (55,56), where it is converted to succinate. Examination of proteins involved in putrescine degradation suggested that this pathway is also active in Synechocystis (Fig.…”
Section: Alternate Pathway For Assimilation Of Nitrogen and Carbon Unmentioning
confidence: 99%